Fifty years without a name: a new species of Splendeuptychia Forster (Lepidoptera: Nymphalidae: Satyrinae) - Rosa, Augusto H. B.; Huertas, Blanca; Willmott, Keith R.; Barbosa, Eduardo P.; Machado, Patrícia A.; Mielke, Olaf H. H.; Canaan, Carlos H. P.; Freitas, André V.l. (Zootaxa, 2021)
A new satyrine butterfly species, Splendeuptychia tupinamba Freitas, Huertas & Rosa, sp. nov. (Nymphalidae: Satyrinae), is described. This species is found throughout a large geographical range in Brazil, Argentina and Paraguay, predominantly in the Cerrado domain, with some records in neighboring Amazonia and Atlantic Forest. Morphology and molecular data indicate that this species is part of a clade that includes Splendeuptychia ashna (the type species of the genus Splendeuptychia), and several species placed in the recently described genus Nubila Viloria, Andrade & Henao, 2019.